Warehouse Administration Process in Companies in West Java - Azzahra, Fadila Hadiputri; Nazarrio, Ahmad; Fatimah Malini Lubis (Journal of Current Research In Multidisciplinary, 2024)
The warehouse is an important asset for the company, as is the warehouse administration process. If the warehouse administration process does not run well, each company will experience inaccuracy in calculating the stock of goods in the warehouse. Furthermore, warehouse administration plays a crucial role in streamlining the processing and management of goods data. In the warehouse administration process in companies in West Java, of course, there are several obstacles, such as inaccurate data accuracy, the process of recording the number of products, the process of checking products, the process of storing products, and the incompatibility of the requested goods with the goods sent. so that a warehouse must really implement an effective and efficient warehouse administration system to help smooth its business. The company devises various solutions to overcome obstacles. The goal of this study is to examine the warehouse administration strategies employed by companies in West Java. This study employs a literature review method, examining several Indonesian journals. The study's findings show that companies in West Java use a variety of warehouse management techniques, such as first-in, first-out (FIFO), perpetual, periodic, average, and class-based storage. For several of these methods, there are advantages and disadvantages.